2004
DOI: 10.1158/0008-5472.can-04-2442
|View full text |Cite
|
Sign up to set email alerts
|

Androgen-Independent Prostate Cancer Is a Heterogeneous Group of Diseases

Abstract: Understanding the biology of prostate cancer metastasis has been limited by the lack of tissue for study. We studied the clinical data, distribution of prostate cancer involvement, morphology, immunophenotypes, and gene expression from 30 rapid autopsies of men who died of hormonerefractory prostate cancer. A tissue microarray was constructed and quantitatively evaluated for expression of prostate-specific antigen, androgen receptor, chromogranin, synaptophysin, MIB-1, and ␣-methylacylCoA-racemase markers. Hie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
447
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 577 publications
(480 citation statements)
references
References 35 publications
22
447
2
Order By: Relevance
“…No association was found between WNT7b expression and bone phenotype in patients with bone metastases. However, WNT7b is known to activate Wnt canonical signaling in osteoblasts (Zhang et al, 2004;Hu et al, 2005), and prostate cancer bone metastases is known to be heterogeneous (Shah et al, 2004), and so WNT7b could be involved in prostate cancer-induced new bone formation in a subpopulation of patients.…”
Section: Lrp5 Mediates Prostate Cancer-induced New Bone Formationmentioning
confidence: 99%
“…No association was found between WNT7b expression and bone phenotype in patients with bone metastases. However, WNT7b is known to activate Wnt canonical signaling in osteoblasts (Zhang et al, 2004;Hu et al, 2005), and prostate cancer bone metastases is known to be heterogeneous (Shah et al, 2004), and so WNT7b could be involved in prostate cancer-induced new bone formation in a subpopulation of patients.…”
Section: Lrp5 Mediates Prostate Cancer-induced New Bone Formationmentioning
confidence: 99%
“…Additional evidence suggests that PSA may have a significant role in osteoblastic bone metastasis (Nelson et al, 1995;Shah et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple mechanisms have been identified that contribute to the androgen sensitive (AS) transition to the AI phenotype [1][2][3][4][5]. In the outlaw pathway, receptor tyrosine kinases are activated, and the androgen receptor (AR) is phosphorylated by either the AKT (protein kinase B) or the mitogen-activated protein kinase (MAPK) pathway, producing a ligand-independent AR.…”
Section: Introductionmentioning
confidence: 99%